Does herding behavior exist in China's carbon markets?. (15th February 2022) - Zhou, Xinxing; Gao, Yan; Wang, Ping; Zhu, Bangzhu; Wu, Zhanchi
Highlights: The first to examine the herding behavior in China's eight carbon markets. Beijing, Shanghai, Chongqing, Fujian four carbon markets exist herding behavior. There is no herding behavior in China's overall carbon market. Herding intensity is positively correlated with carbon market volatility. Abstract: This paper introduces a modified cross-sectional absolute deviation approach to measure the existence of herding behavior and herding asymmetry, and uses the runs test to measure the herding intensity in China's carbon markets. It is the first study to examine the existence of herding behavior in China's carbon markets. The empirical results show that no herding behavior exists in China's overall carbon market. As for herding asymmetry, no herding behavior exists in both up and down markets and in the markets with high and low trading volumes, as well as in the markets with high volatility. Among China's eight carbon markets, herding behavior exists in Beijing, Shanghai, Chongqing, and Fujian, in which Chongqing has the highest herding intensity, while Guangdong, Hubei, Shenzhen, and Tianjin have no herding behavior. The herding behavior is prone to the occurrence when carbon price continuously rises or falls with high volatility. When the carbon market is highly volatile with a large transaction volume, the herding intensity is high. Herding intensity is positively correlated with market volatility. Finally, we propose policy implications to mitigate herding behavior.